Implementation of Game-Based Learning Using Classcraft in Spreadsheet Instruction to Enhance Collaboration Among Accounting Vocational High School Students - Wahyuni, Rika (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2025)
This study evaluates the effectiveness of Game-Based Learning using the Classcraft platform in enhancing students’ collaboration skills in Spreadsheet learning at Accounting Vocational Schools. The main issue addressed is the low student participation and collaboration in a subject often seen as technical and monotonous. Employing Kemmis and McTaggart’s Classroom Action Research model, the study was conducted over two cycles involving class X students at SMK Muhammadiyah 3 Singosari. Data were gathered through observation, questionnaires, tests, and documentation. Results showed an increase in collaboration skills from 64% (“sufficient”) in cycle I to 82% (“good”) in cycle II. Student learning completion also rose from 57% to 89%. Classcraft successfully fostered positive group interdependence, motivation, and engagement. These findings suggest that Classcraft is an effective, innovative tool for promoting collaboration in technical subjects like Spreadsheet learning.